(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Rhinoplasty is a complex intervention aimed at enhancing both nasal aesthetics and functionality. The literature underscores the occurrence of adverse events in this procedure, prompting the search for effective correction strategies. In this context, otorhinolaryngology plays a crucial role, with a fundamental need to comprehend the incidence and types of complications to improve clinical practices. Methods: A systematic literature review was conducted to identify studies addressing adverse events in rhinoplasties and the role of otorhinolaryngology in their correction. The consulted databases included PubMed, Scopus, SciELO, Cochrane Library, LILACS, and Embase. Keywords such as "Rhinoplasty," "Otorhinolaryngology," "Adverse events," "Aesthetic outcomes," "Functional outcomes," "Nasal surgery," and "Complications in rhinoplasty" were combined using boolean operators "OR" and "AND." Results: The compiled results reveal a variety of adverse events in rhinoplasties, ranging from aesthetic complications to functional challenges. The analysis underscores the importance of a specialized otorhinolaryngological approach in minimizing these adverse events, emphasizing the need for treatment personalization to optimize outcomes. Conclusion: It is concluded that otorhinolaryngology plays an essential role in correcting adverse events in rhinoplasties. The systematic review highlights the complexity of these interventions, emphasizing the necessity of a multidisciplinary and specialized approach to achieve satisfactory aesthetic and functional outcomes. These findings support the significance of the otorhinolaryngologist’s role in optimizing the quality of care provided to patients undergoing rhinoplasties.